Drought tolerance of Aspergillus violaceofuscus and Bacillus licheniformis and their influence on tomato growth and potassium uptake in mica amended tropical soils under water-limiting conditions - Muthuraja, Raji; Muthukumar, Thangavelu; Natthapol, Chittamart (Frontiers in Plant Science, 2023)
Drought is a significant abiotic stress that alters plant physiology and ultimately affects crop productivity. Among essential plant nutrients, potassium (K) is known to mitigate the deleterious effect of drought on plant growth. If so, K addition or inoculation of potassium solubilizing microorganisms (KSMs) that are tolerant to drought should promote plant growth during water stress. Therefore, in this study, K solubilizing Aspergillus violaceofuscus and Bacillus licheniformis, isolated from saxicolous environments, were tested for their capacity to tolerate drought using different molecular weights (~4000, 6000, and 8000 Da), and concentrations (0, 0.25, 0.50, 0.75, 1.0, and 1.25 g/L) of polyethylene glycol (PEG) under in vitro conditions. The results showed that high concentrations (0.75 and 1.0 g/L) of different molecular weight PEG considerably improved bacterial cell numbers/fungal biomass and catalase (CAT) and proline activities. Moreover, the ability of KSMs alone or in combination to impart drought tolerance and promote plant growth in the presence and absence of mica (9.3% K2O) supplementation was tested in Alfisol and Vertisol soil types under greenhouse conditions. The results revealed that the tomato plants inoculated with KSMs individually or dully with/without mica improved the physiological and morphological traits of the tomato plants under drought. Generally, tomato plants co-inoculated with KSMs and supplemented with mica were taller (2.62 and 3.38-fold) and had more leaf area (2.03 and 1.98-fold), total root length (3.26 and 8.86-fold), shoot biomass (3.87 and 3.93-fold), root biomass (9.00 and 7.24-fold), shoot K content (3.08 and 3.62-fold), root K content (3.39 and 2.03-fold), relative water content (1.51 and 1.27-fold), catalase (2.11 and 2.14-fold), proline content (3.41 and 3.28-folds), and total chlorophyll content (1.81 and 1.90-fold), in unsterilized Alfisol and Vertisol soil types, respectively, than uninoculated ones. Dual inoculation of the KSMs along with mica amendment, also improved the endorrhizal symbiosis of tomato plants more than their individual inoculation or application in both soil types. These findings imply that the Aspergillus violaceofuscus and Bacillus licheniformis isolates are promising as novel bioinoculants for improving crop growth and yield in water-stressed and rainfed areas of the Tropics in the future.